ASSESSMENT OF MALE REPRODUCTIVE HEALTH BY CONVENTIONAL METHOD OF SEMEN ANALYSIS - Khan, Mohammad Shoaib; Deepa, Fariyal; Ahmed, Zahoor; Tahir, Fahim; Khan, Mudassir Ahmad (Journal of Ayub Medical College Abbottabad, 2011)
Background: Data available over the past twenty years reveal that in approximately 30% of cases of infertility, pathology is found in man alone, and in another 20% both man and woman are abnormal. Therefore, the male factor is at least partly responsible in about 50% of infertile couples. The longer a couple remains sub fertile, the worse is their chance for an effective cure. This study was planned to analyse the complete semen picture of infertile men for assigning the specific cause to male infertility related to concentration, motility and morphology and to know the distribution and pattern of male infertility in the various subclasses in Pakistani population. Methods: It was a prospective descriptive analytical study conducted at Department of Reproductive Physiology/ Health, Public Health Divisions, National Institute of Health (NIH), Islamabad. One thousand five hundred twenty-one (1,521) infertile male patients, and 97 proven fathers, taken as a control. Conventional semen analysis was performed on all samples. Results: Out of 1,521 infertile men, 13.3% were azoospermic, 23.2% oligozoospermic, 0.9% polyzoospermic, 14.5% normozoospermic, 35.2% asthenozoospermic 10.5% oligoasthenozoospermic and 2.4% teratozoospermic. Sperm concentration and active motility of proven fathers, was significantly higher (p<0.05) than the normal concentration group. Least liquefaction time was recorded in case of polyzoospermic subjects, and highest for azoospermic cases. Although, the liquefaction time of azoospermic and oligozoospermic subjects varied non-significantly (p>0.05) with the proven fathers. Normal forms were significantly higher (p<0.05) among the proven fathers and polyzoospermic cases, in comparison with the other groups. Head defects were more in teratozoospermic group, followed by oligoasthenozoospermic and oligozoospermic patients. Neck defects were more profound in oligoasthenozoospermic and oligozoospermic patients, while, tail defect showed significant increase in teratozoospermic and asthenozoospermic cases only. Head and neck defect varied significantly (p<0.05) with proven fathers in all groups, while tail defect varied significantly (p<0.05) in oligozoospermic, asthenozoospermic and teratozoospermic groups only when compared with proven fathers. Conclusions: Complete semen analysis which provides important information about the quality and quantity of the sperm, should be performed before reaching a final conclusion. Keywords: Semen analysis, male infertility, Pakistani population